1996
DOI: 10.1097/00005131-199611000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Thoracolumbar Burst Fractures Without Neurological Deficit

Abstract: Thoracolumbar burst fractures are a major cause of disability; however, there are few studies on the functional outcome of patients with this injury. The purpose of this study is to evaluate the functional outcome of patients with thoracolumbar burst fractures using a generic and a condition-specific health status survey. The SF-36 survey (generic) and the Roland scale (condition-specific) were administered to 24 patients who had a minimum of 2 years follow-up after a thoracolumbar burst fracture without neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
100
1
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(117 citation statements)
references
References 15 publications
6
100
1
10
Order By: Relevance
“…Reid et al [38] reported that much of this progression also appears to occur in the initial period after injury, with relative stabilization of kyphosis within 12 to 18 months. Furthermore, our meta-analysis showed no association between degree of kyphosis and pain and function, which is consistent with findings from other studies [10,12,13,27,34,47,51]. There is limited evidence that pain is more common with a kyphotic angle greater than 30° [22,49], a level of deformity that vastly exceeded the mean kyphosis observed at last followup in operatively and nonoperatively treated patients in our analysis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Reid et al [38] reported that much of this progression also appears to occur in the initial period after injury, with relative stabilization of kyphosis within 12 to 18 months. Furthermore, our meta-analysis showed no association between degree of kyphosis and pain and function, which is consistent with findings from other studies [10,12,13,27,34,47,51]. There is limited evidence that pain is more common with a kyphotic angle greater than 30° [22,49], a level of deformity that vastly exceeded the mean kyphosis observed at last followup in operatively and nonoperatively treated patients in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…There is limited evidence that pain is more common with a kyphotic angle greater than 30° [22,49], a level of deformity that vastly exceeded the mean kyphosis observed at last followup in operatively and nonoperatively treated patients in our analysis. Therefore although kyphosis is a common outcome measure in the literature, the importance attributed to this anatomic parameter in studies is difficult to justify, as its clinical importance is questionable [27,43,50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations